Dating of an alpine ice core from the interior of the Tibetan Plateau. (10th April 2020) - Shao, Lili; Tian, Lide; Wu, Guangjian; Naftz, David; Cai, Zhongyin; Wang, Cheng; Li, Yao; Palcsu, László
Abstract: Accurate archive-based paleoclimate reconstruction requires precise dating. However, the dating of mid- and low-latitude alpine ice cores is in challenge, in particular for the lower parts of ice cores. Here, we present a new dating work for a 109 m ice core collected to bedrock from the Qiangtang No. 1 glacier, central Tibetan Plateau. Annual layer counting based on seasonal indicators, in combination with absolute dating of radioactivity peaks, indicates that the upper part (0–79 m) captures a period of 678 years from 1334–2011 AD, with an uncertainty of ±20 years at 79 m. In the lower part (79–109 m), we dated by visible annual layer thickness-depth relationships and found the lower ice core captures 665 years of deposition and can be dated back to 669 ± 66 AD at 109 m. This new method reduces the ambiguity of utilizing glacier flow models that have been widely used in previous study. On the presence of observable optical annual layers, the polynomial fitting method based on annual layer thickness-depth relationships is a superior method to obtain reliable chronology in the lower parts. Furthermore, this method has the potential to improve the dating of other alpine ice cores with similar settings.